Proceeding of Fourth International Conference on Spoken Language Processing. ICSLP '96
DOI: 10.1109/icslp.1996.608020
|View full text |Cite
|
Sign up to set email alerts
|

The Nemours database of dysarthric speech

Abstract: The Nemours database is a collection of 814 short nonsense sentences; 74 sentences spoken by each of 11 male speakers with varying degrees of dysarthria. Additionally, the database contains two connected-speech paragraphs produced by each of the 11 speakers. The database was designed to test the intelligibility of dysarthric speech before and after enhancement by various signal processing methods, and is available on CD-ROM. It can also be used to investigate general characteristics of dysarthric speech such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 5 publications
0
96
0
Order By: Relevance
“…Regarding disordered speech, some previous corpora have been acquired for studies in dysarthic speech like Nemours (Menéndez-Pidal et al, 1996), a research corpus of 814 short sentences in English from 11 dysarthric speakers, and the corpus for the STARDUST project (Hawley et al, 2003) (Kim et al, 2008) is a massive corpus containing several hours of speech from 10 individuals with different degrees of dysarthria. In languages different from English, it can be referred also efforts of speech acquistion in Dutch (Sanders et al, 2002), and regarding Spanish, the most remarkable effort was done in the HACRO project (Navarro-Mesa et al, 2005), containing speech from speakers of different ages with different speech impairments for the development of a tool for the evaluation of oral utterances.…”
Section: A Novel Corpus Of Impaired Speech From Children and Young Admentioning
confidence: 99%
“…Regarding disordered speech, some previous corpora have been acquired for studies in dysarthic speech like Nemours (Menéndez-Pidal et al, 1996), a research corpus of 814 short sentences in English from 11 dysarthric speakers, and the corpus for the STARDUST project (Hawley et al, 2003) (Kim et al, 2008) is a massive corpus containing several hours of speech from 10 individuals with different degrees of dysarthria. In languages different from English, it can be referred also efforts of speech acquistion in Dutch (Sanders et al, 2002), and regarding Spanish, the most remarkable effort was done in the HACRO project (Navarro-Mesa et al, 2005), containing speech from speakers of different ages with different speech impairments for the development of a tool for the evaluation of oral utterances.…”
Section: A Novel Corpus Of Impaired Speech From Children and Young Admentioning
confidence: 99%
“…Past ASR experiments on dysarthric speech mostly included GMM-HMM systems [15][16][17][18][19][20]. More recently Lee et al [21] reported ASR performance on Cantonese aphasic speech and disordered voice.…”
Section: Introductionmentioning
confidence: 99%
“…The single word stimuli in the database include repetitions of English digits, the international radio alphabets, the 20 most frequent words in the British National Corpus (BNC), and a set of words selected to demonstrate relevant phonetic contrasts [21]. Other databases such as UA-Speech database [22] or Nemours database [23] mainly contain isolated words, acoustic samples of digits, radio alphabet letters, and computer commands, which is inadequate to build a continuous dysarthric speech recognition model.…”
Section: Materials and Feature Descriptionmentioning
confidence: 99%